PANDANGAN KRITIS ISLAM LIBERAL ATAS ISU-ISU KONTEMPORER - Muhammad Taufik (Pascasarjana UIN ANTASARI Banjarmasin, 2015)
Islam is believed not to be in the contrary of humanity and universal values;justice, virtue and equality. However, it cannot be denied that the reality ofcurrent social life of Islam is still marked imbalances. Therefore, it needsserious excavation in rediscovering the spirit of rahmatan lil Alamin asauthentic Islam. This paper discusses the views of liberal Islamic groups inrelation to the position of women in traditional Islamic societies, especiallythe issue of polygamy, inheritance rights, women as heads of state, womenas imam in the congregational prayers, and the obligation of hijab